1988
DOI: 10.1159/000153775
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Two Serum Proteins Haptoglobin and Transferrin and Leukaemia

Abstract: Haptoglobin and transferrin (TF) types were determined for 134 patients with leukaemia of the four most common types: acute lymphocytic (ALL), chronic lymphocytic (CLL), acute myelocytic (AML) and chronic myelocytic leukaemia (CML). The phenotype HPl was found to have an increased incidence in the total patient group due to an increased incidence in those with AML, ALL and CML compared with controls, but not in those with CLL. Although tests of association applied to each of the samples of the four common type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 15 publications
(19 reference statements)
2
15
1
Order By: Relevance
“…Because the expression of BCR/ABL stimulates ROS production, which may contribute to increased DNA damage in CML cells (Sattler et al, 2000;Nowicki et al, 2004), the Hp polymorphism has been investigated in leukemias, and the Hp1-1 phenotype has been associated with increased risk (Nevo and Tatarsky, 1986;Mitchell et al, 1988;Campregher et al, 2004). Despite the small sample size and large confidence interval, results indicated increased CML risk for Hp1F-1S individuals of black skin color and decreased risk for the same group carrying the Hp1S-2 genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the expression of BCR/ABL stimulates ROS production, which may contribute to increased DNA damage in CML cells (Sattler et al, 2000;Nowicki et al, 2004), the Hp polymorphism has been investigated in leukemias, and the Hp1-1 phenotype has been associated with increased risk (Nevo and Tatarsky, 1986;Mitchell et al, 1988;Campregher et al, 2004). Despite the small sample size and large confidence interval, results indicated increased CML risk for Hp1F-1S individuals of black skin color and decreased risk for the same group carrying the Hp1S-2 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the BCR/ABL expression stimulates ROS production in hematopoietic progenitor cells (Sattler et al, 2000) and studies have suggested that ROS may contribute to increased DNA damage in CML cells (Nowicki et al, 2004). Because the ability of Hp to block hemoglobin-induced oxidative stress and damage is phenotype dependent (Carter and Worwood, 2007), Hp polymorphism has been investigated in association with leukemia, and the Hp1-1 phenotype has been associated with CML, acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) (Nevo and Tatarsky, 1986;Mitchell et al, 1988). However, the frequency distributions of Hp phenotypes and alleles vary among populations worldwide (Carter and Worwood, 2007), so it is important to run further association studies with CML in different ethnic groups to better evaluate these risks.…”
Section: Introductionmentioning
confidence: 99%
“…[58] It has also been investigated with leukemia, and the Hp1-1 phenotype associated with CML, acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL). [58,59] Recently, Hp polymorphism has also been suggested as a determining factor in runners' performance. [44] In our previous studies, deviation from HWE was mainly due to higher than expected frequency of Hp1F-1F and 1S-1S contrasting with lower frequency of Hp1F-1S.…”
Section: Wwwantioxorg Discussionmentioning
confidence: 99%
“…In humans, the HP locus is polymorphic, with two codominant alleles (HP1 and HP2) that yield three distinct genotypes/phenotypes (Hp1-1, Hp2-1 and Hp2-2) (Sadrzadeh and Bozorgmehr, 2004). Elevated levels of haptoglobin have been demonstrated in lung cancer (Beckman et al, 1986), bladder cancer (Benkmann et al, 1987), leukemia (Mitchell et al, 1988), breast cancer (Awadallah and Atoum, 2004), malignant lymphoma (Epelbaum et al, 1998), urogenital tumors (Dunzendorfer et al, 1980), esophageal squamous cell carcinoma , ovarian cancer (Zhao et al, 2007) and gliomas (Kumar et al, 2010).…”
Section: Elevated Serum Haptoglobin Is Associated With Clinical Outcomentioning
confidence: 99%